2002
DOI: 10.1111/1540-627x.00060
|View full text |Cite
|
Sign up to set email alerts
|

Craft Retailers' Criteria for Success and Associated Business Strategies

Abstract: This research was designed to fill the void in understanding how art-related retailers define and achieve success. A two-phase data collection process was implemented. Preliminary personal interviews were conducted with 12 craft retailers followed by a mailed survey to 1000 craft retailers in nine southeastern U.S. states. Factor analysis was employed to reduce the number of items for defining success. Cluster analysis followed to develop empirical groupings of craft retail businesses based on the success fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
2
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(186 citation statements)
references
References 18 publications
6
160
2
18
Order By: Relevance
“…Thus, it is about time to identify what factors influence women entrepreneurs' success in small business in Malaysia. According to Paige and Littrell (2002) success is defined by intrinsic criteria include freedom and independence, controlling a person's own future, and being one's own boss; whilst extrinsic outcomes are, among others, increased financial returns, personal income, and wealth. On the other hand, research by Masuo et al (2001) found that business success is commonly defined in terms of economic or financial measures which include return on assets, sales, profits, employees and survival rates; and non-pecuniary measures, such as customer satisfaction, personal development and personal achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it is about time to identify what factors influence women entrepreneurs' success in small business in Malaysia. According to Paige and Littrell (2002) success is defined by intrinsic criteria include freedom and independence, controlling a person's own future, and being one's own boss; whilst extrinsic outcomes are, among others, increased financial returns, personal income, and wealth. On the other hand, research by Masuo et al (2001) found that business success is commonly defined in terms of economic or financial measures which include return on assets, sales, profits, employees and survival rates; and non-pecuniary measures, such as customer satisfaction, personal development and personal achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mental agony scales' reliability coefficients ranged from 0.924 to 0.925. While the reliability score of the MSP scale was 0.884 (Nunnally, 1978;Paige & Littrell, 2002). The results of validity testing show that discriminative indices ranged from 34.331 to 41.663 (The statistical significance for all tests was a 0.001 level of confidence).…”
Section: Research Instruments and Quality Testingmentioning
confidence: 98%
“…This argument is based on the fact that every organization has its different characteristics, goals and constituencies. Paige and Littrell (2002) assert that some scholars include subjective (intrinsic) criteria such as freedom and independence, being one's own boss, controlling one's own future; while the objective (extrinsic) factors such as increased profitability and wealth as the criteria for organizational survival. Cameron (1978) suggested that there are other criteria that could be used in the measurement of organizational survival such as effectiveness and efficiency.…”
Section: Edwinah Amah 69mentioning
confidence: 99%